The use of an Estuarine System (Mondego estuary, Portugal) as Didactic Tool to incorporate Education for Sustainable Development into School Curricula - Costa,Sónia (2013)
The present paper reviews and discusses the use of the Mondego estuary (Portugal) ecosystem as educational tool for science and environmental teachers/educators. The Mondego estuary is a coastal area of acknowledged high socioeconomic and environmental value (National Ecological Reserve, Important Bird Area and RAMSAR site) whose characteristics (e.g. two distinct subsystems with different physicochemical and ecological characteristics, strong environmental gradients, and anthropogenic pressures) have been used for educational purposes. However, besides the vast available scientific output focused in the Mondego estuary, few had the focal point in its pedagogical potentialities (were only published three MSc dissertations and two book chapters in books of Environmental Education incorporating teaching strategies to approach issues, behind different educational perspectives). The Mondego estuary is presented here as an ecosystem that can be used for educational purposes related to ecology, conservation biology, and sustainability in the coastal zone. In order to use the Mondego estuarine system under an educational framework, some examples of tools to address the pedagogical potentialities, like interpretative routes, analysis of scientific texts, and teachers training programs are presented.